Collaboration among governments, agribusinesses, and rural households for improving the effectiveness of conservation tillage technology adoption - Shanshan Miao; Binghong Chen; Naihua Jiang (Scientific Reports)
Abstract Conservation tillage technology adoption has contributed significantly to sustainable agricultural development, but its effectiveness has been hindered by conflicts among governments, agribusinesses, and rural households. The collaboration among governments, agribusinesses, and rural households (GAR collaboration) is a significant institutional innovation for advancing green agricultural development. This study constructs a theoretical framework incorporating environmental characteristics, collaboration capacity, and the effectiveness of green agricultural technology adoption to analyze the impact and heterogeneity effects of GAR collaboration. Using village-level survey data from Shaanxi, Ningxia, and Gansu Provinces, with a focus on conservation tillage technology, this study explores the mechanisms by which GAR collaboration influences green technology adoption. The findings reveal that: (1) GAR collaboration mechanisms are crucial for improving the effectiveness of green agricultural technology adoption; (2) Environmental characteristics directly affect the adoption effectiveness and indirectly influence it through collaboration capacity; (3) Village size has a heterogeneous effect on the impact of GAR collaboration, being more pronounced in smaller villages; and (4) GAR collaboration primarily enhances the adoption effectiveness by reducing transaction costs and defection risks. These insights contribute to the theoretical foundations of collaborative approaches in green agriculture and provide practical solutions to improve technology adoption.